“H.I.M.’s Armourer Geurk”. Concerning the title of Geurk Eliarov - Levan B. Dvalishvili (Историческое оружиеведение)
The Eliarov armourers are most often remembered for the golden inscription on their blades: “H.I.M.’s Armourer Geurk” (His Imperial Majesty’s Armourer Geurk). The inscription hints that Geurk and his sons Karaman and Ephraim apparently held the title of imperial armourers, yet this fact has not been supported by official documentary evidence to date. The purpose of the article is to introduce several previously unknown sources that make it possible to establish the date of Geurk receiving the title of imperial armourer and to confirm that his sons also possessed this title after their father’s death.